45th UID Conference (diségno, 2024)
The 45th International Conference of Representation Disciplines Teachers, Congress of Unione Italiana per il Disegno (UID), promoted the close collaboration between the University of Padua and the Iuav University of Venice in promoting the dialogue, the sharing, and the planning linked to the science of drawing. In three intense days of study, the two cities hosted more than 350 scholars (including professors, researchers, PhDs, designers and drafters), from Italy and as well as from other countries. They exchanged views, reflecting on the notion of measurement and/or unmeasurement related to the discipline of drawing. [read more]